2011
DOI: 10.1038/eye.2011.97
|View full text |Cite
|
Sign up to set email alerts
|

Primary open-angle glaucoma genes

Abstract: A substantial fraction of glaucoma has a genetic basis. About 5% of primary open angle glaucoma (POAG) is currently attributed to single-gene or Mendelian forms of glaucoma (ie glaucoma caused by mutations in myocilin or optineurin). Mutations in these genes have a high likelihood of leading to glaucoma and are rarely seen in normal subjects. Other cases of POAG have a more complex genetic basis and are caused by the combined effects of many genetic and environmental risk factors, each of which do not act alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
175
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(187 citation statements)
references
References 76 publications
(98 reference statements)
2
175
1
2
Order By: Relevance
“…Genes that may play an important role in the pathogenesis of POAG have been intensively investigated. Different approaches are being used to study the genetics of this type of glaucoma, offering new insights into the pathogenesis of this disease (Fingert, 2011). Recent studies examining POAG in Caucasian populations from the United States revealed that disease susceptibility was linked to the GLC1I locus on chromosome 15q (Allingham et al, 2005;Woodroffe et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Genes that may play an important role in the pathogenesis of POAG have been intensively investigated. Different approaches are being used to study the genetics of this type of glaucoma, offering new insights into the pathogenesis of this disease (Fingert, 2011). Recent studies examining POAG in Caucasian populations from the United States revealed that disease susceptibility was linked to the GLC1I locus on chromosome 15q (Allingham et al, 2005;Woodroffe et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly associated with normal tension glaucoma, optineurin mutations have also been linked to POAG [17]. Together, mutations within the optineurin and myocilin genes have been encountered in up to 5% of adult-onset cases of POAG [18].…”
Section: Genes Associated With Poagmentioning
confidence: 99%
“…Some even leave the eye behind in order to venture into the Central Nervous System in search of an explanation. Currently, glaucoma is seen either as a hereditary degenerative disorder [20], a CNS disease [21] or as an autoimmune process [22], among other labels.…”
Section: Glaucoma: How Many Different Diseases?mentioning
confidence: 99%